Influência da taxa de aquecimento do tratamento térmico final da microestrutura e textura do aço inoxidável ferrítico AISI 430 estabilizado ao nióbio - Daniella Gomes Rodrigues (2013)
The influence of the heating rate of final annealing on the microstructure, texture and mechanical properties were studied for a niobium ferritic stainless steel. The material was manufactured industrially and was cold rolled to an 85% reduction in thickness. The cold rolled specimens were annealed at 880°C, applying 0.10, 6.8, 23.5, and 41.5ºC/s heating rates and a soaking time of 24s. The annealing was interrupted at 780, 830, and 880 ºC to monitor the progress of the microstructure and texture. The increase in the heating rate reduced the size of the recrystallized grain, increased the onset recrystallization temperature besides this, increased the yield strength and the tensile strength. By contrast, it reduced the volume fraction of the -fiber and increased the volume fraction of the Goss component and random orientation. For the sheet annealed at a heating rate of the 0.10°C/s, the average value was notably higher, =1.99. The ratio between the {111} and {001} volume fractions of planes parallels to the surface, {111}/{001}, decreased with increasing heating rates, presenting a maximum value of 5.17 for 0.10°C/s. The roping level didnt show a significant difference with the change in heating rate.